Analis Kemampuan Menulis Teks Eksposisi Siswa Kelas V SD - Nurrahma Zulita; Chandra Chandra; Inggria Kharisma (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to describe the ability to write exposition texts for 5th grade elementary school students, before and after the implementation of the Think-Pair-Share strategy. This study uses a descriptive qualitative approach. The subjects of the study were 7 5th grade students of SD Negeri which totaled 7 students. Data is collected through observation of the learning process and analysis of students' writing. The results showed that before the implementation of the Think-Pair-Share strategy, most students had the ability to write exposition texts in adequate categories. After the implementation of the Think-Pair-Share strategy, there was an increase in students' ability to write exposition texts, with most students in the good category. This study concludes that the Think-Pair-Share strategy can make a positive contribution in improving the ability to write exposition texts for grade 5 elementary school students